PENERAPAN PENDEKATAN WHOLE LANGUAGE DALAM MENINGKATKAN KETERAMPILAN BERBAHASA INDONESIA SISWA DI SEKOLAH DASAR : SYSTEMATIC LITERATURE RIVIEW - Triana, Dea; Nurul Hidayah; Ayu Reza Ningrum; Diah Rizki Nur Khalifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the implementation of the Whole Language approach in improving Indonesian language skills of elementary school students through a Systematic Literature Review (SLR). The Whole Language approach emphasizes holistic language learning, where listening, speaking, reading, and writing skills are developed integratively within meaningful contexts. This study analyzed scientific articles published between 2020 and 2024 obtained from reputable academic databases. The review of seven selected articles that met the inclusion criteria revealed that the implementation of the Whole Language approach significantly enhances Indonesian language skills among elementary students, particularly in reading comprehension, creative writing, and communicative speaking. Moreover, this approach creates an enjoyable, interactive, and contextual learning environment that motivates students to actively use the Indonesian language. Therefore, Whole Language can be recommended as an effective instructional strategy to improve Indonesian language skills at the elementary school level.